Survival and factors related to death of patients with head and neck câncer (Research, Society and Development, 2022)
Introduction: Head and neck cancer is considered one of the most aggressive cancers, with low survival and a negative impact on patients' quality of life. Objetives: To evaluate the survival and death-related factors of patients with head and neck cancer in the State of Sergipe. Methods: Longitudinal study with patients diagnosed with head and neck cancer from August 2017 to June 2020. The minimum sample size was estimated at 47 patients, based on a non-parametric survival analysis of a sample. Data were examined for loss to follow-up, outliers, normality and linearity. Survival was calculated using the Kaplan-Meier limit product estimator, factors related to death by Cox regression. Results: Of the 79 patients followed, most were men, mean age 55 years, residents of the interior of the state, low income and schooling, smokers and diagnosed with advanced stage injuries. Overall survival at 12 and 24 months of follow-up was 50.6% and 39.4%, respectively. Being male and not having a partner was associated with death. Conclusion: Patients with head and neck cancer in Sergipe have a low 24-month survival and a higher risk of death among male and single, divorced and widowed individuals.